Audio CD & multimedia CD-Rom production : Capriccio. - Kay, Hui Hong. (2008)
The goals of this project are to acquire skills in producing an audio CD and a multimedia CD-ROM, and to increase awareness and interest of Chinese orchestral music among people, particularly the young generation.